Respuesta :

yazan6
The limit does not exist
Ver imagen yazan6
msm555

Answer:

Solution given:

[tex]Lim_{h\rightarrow} \frac{\sqrt{x+h}-\sqrt{x}}{h}[/tex]

The given expression takes the form of [tex]\frac{0}{0}[/tex]

when h=0

now

[tex]lim_{h\rightarrow 0} \frac{\sqrt{x+h}-\sqrt{x}}{h}*\frac{\sqrt{x+h}+\sqrt{x}}{\sqrt{x+h}+\sqrt{x}}[/tex]

[tex]lim_{h\rightarrow 0}\frac{(x+h)-x}{h*({\sqrt{x+h}+\sqrt{x}})}[/tex]

[tex]lim_{h\rightarrow 0}\frac{h}{h*({\sqrt{x+h}+\sqrt{x}})}[/tex]

[tex]lim_{h\rightarrow 0}\frac{1}{({\sqrt{x+h}+\sqrt{x}})}[/tex]

=[tex]\frac{1}{\sqrt{x+0}+\sqrt{x}}[/tex]

=[tex]\frac{1}{2\sqrt{x}}[/tex]